Optimalisasi Perkembangan Motorik Anak Melalui Aktivitas Berbasis Bermain Di Taman Kanak-Kanak - Maesaroh Maesaroh; Refyna Nurwanti Kurniawan; Risma Nadhitul Izmah; Salma Nur Septiani; Sindi Agustin (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study is motivated by the limited integration of play-based motor stimulation with Islamic educational values in early childhood education, as well as the lack of holistic studies examining planning through evaluation processes. The research problem focuses on how motor development activities are planned, implemented, and evaluated through play-based learning within an Islamic early childhood education perspective. This qualitative descriptive study employed observation, interviews, and documentation in a kindergarten in Tasikmalaya. The findings reveal that motor activities are systematically designed through structured play to stimulate both gross and fine motor skills. The novelty of this study lies in integrating play-based motor activities with Islamic values such as independence, discipline, and responsibility in the learning process. Theoretically, this study contributes to strengthening the holistic-integrative learning framework in Islamic early childhood education. Practically, it offers recommendations for teachers to design structured, meaningful, and value-based motor activities, while emphasizing the importance of parent-teacher collaboration in supporting optimal child development